Incentivizing environmental sustainability for surgical healthcare at a systems level - Elizabeth Christophel; Russell Seth Martins; Kyle Tafuri; Faiz Y. Bhora (BMC Surgery)
Abstract The healthcare sector contributes up to 4.6% of global greenhouse gas emissions. The surgical system contributes predominantly. Despite this, many hospitals have been slow to adopt sustainable practices. This editorial discusses strategies to incentivize surgical healthcare systems to prioritize more sustainable operations, using examples from other industries as well as healthcare systems from more sustainable nations.